Of youth-harps and songbirds: the sweet music of Wasulu - Maxwell, Heather A. (International Library of African Music, 2008)
In 1992 the West African nation of Mali proudly became a democratic republic under the leadership of the dynamic president, Alpha Oumar Konare. With this political transition came a host of dramatic cultural changes in the nation's capital, Bamako. One such change was a new kind of music called wassoulou. Gritty and funky, yet deeply rooted in the Wasulu traditions of Mali's southeastern heartland, wassoulou and its brilliant female singers carried a new voice to Bamako and beyond: a democratic voice that expressed fresh, youthful, and feminine perspectives about life. In the early 1990s, this new sound invaded the nation's commercial music sector, radio, and television with astounding success and swiftly became the driving musical force in popular culture.
Keywords: African Music